Línea Sur 6 : foreign policy journal sep/dec 2013
With this sexth editon of Línea Sur, the Foreign Policy Journal, entitled" Security and Human Rights, " we are surely movin forward with the circulaations and implemtación of an alternative contribution to the debate on contemporaty global issues.